Hubungan Keteraturan Kunjungan Antenatal Care (Anc) Dengan Risiko Anemia Pada Ibu Hamil - Anggraeni, Ayu Kurnia; Rahayu, Antika Maulida (Madu : Jurnal Kesehatan, 2025)
The high maternal mortality rate can be caused by anemia during pregnancy, one contributing factor being irregular Antenatal Care (ANC) visits. This study aims to examine the relationship between the regularity of ANC visits and the risk of anemia in pregnant women at M. Thaha Public Health Center, South Bengkulu. This research employed an analytic survey with a case-control design. Data were obtained from secondary sources with a total sample of 48 respondents. Data were analyzed using univariate and bivariate analysis with the chi-square test, Contingency Coefficient (C), and Odds Ratio (OR). The univariate analysis showed that 20 pregnant women had irregular ANC visits and 24 experienced anemia. The bivariate analysis revealed a moderate relationship between ANC visit regularity and the risk of anemia, with an OR value of 4.2. This indicates that pregnant women with irregular ANC visits are 4.2 times more likely to develop anemia compared to those with regular visits. It is recommended that the health center improve maternal health services by enhancing access to maternal posyandu services and conducting regular hemoglobin (Hb) examinations to detect and control anemia at an early stage.